Access Regulation and Infrastructure Investment in the Mobile Telecommunications Industry - Kim, J.; Kim, Y.; Gaston, Noel; Lestage, R.; Kim, Y.; Flacher, D. (Pergamon, 2011)
While mobile virtual network operators (MVNOs) increase competition in the mobile telecommunications industry, granting market access to MVNOs may have unwanted consequences. In particular, infrastructure investment by incumbent mobile network operators (MNOs) may be smaller. This paper examines the effects of MVNO entry and access regulation on the investment behavior of MNOs. It uses firm-level data for 58 MNOs in 21OECD countries during2000–2008. The results suggest that mandated provision of access is related to lower investment intensity of MNOs, while voluntary access provision as no-effect. Although reduced investment incentives do not necessarily correspond to under-investment, this underscores the need for those countries where MVNOs are provided access to address the issue of investment incentives.